PENGARUH MODEL PROBLEM-BASED LEARNING AND COOPERATIVE LEARNING TIPE THINK-PAIR-SHARE DITINJAU DARI GAYA BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 2 SD ABC [THE EFFECT OF THE THINK-PAIR-SHARE TYPE OF PROBLEM-BASED LEARNING AND COOPERATIVE LEARNING MODEL ON THE CRITICAL THINKING SKILLS OF SECOND GRADE STUDENTS OF ABC SCHOOL] - Jessica Levina; Gusti Yarmi; R. Bambang Aryan Soekisno (Polyglot, 2022)
Critical thinking ability needs to be developed from an early age, so it is very important to find an effective learning model to foster critical thinking skills. The learning model being tested is the Problem-Based Learning and the Cooperative Learning Model Think-Pair-Share (TPS) Type. This study aims to see the effect of the learning model reviewed from learning style on critical thinking skills. This research was conducted in SD ABC with a population of 153 students in grade II. This research method is quantitative research using quasi-experimental. Data analysis was tested using normality and homogeneity tests. Hypothesis testing using two-way ANOVA and Tukey's test. The conclusion obtained is that there are differences in the results of critical thinking skills between students who received learning with Problem-Based Learning and Cooperative Learning Model TPS Type with a significance level of 0.017, there is no difference in students' critical thinking skills with auditory learning styles between those who received learning with Problem-Based Learning and Cooperative Learning Model TPS Type with a significance value of 0.211, and there is no difference in students' critical thinking skills with kinesthetic learning styles between those who received learning with Problem-Based Learning and Cooperative Learning Model TPS Type with a significance value of 0.421.Bahasa Indonesia Abstrak: Kemampuan berpikir kritis perlu dikembangkan sejak dini, maka sangat penting untuk menemukan model pembelajaran yang efektif memupuk kemampuan berpikir kritis. Model pembelajaran yang diujicobakan adalah Model Pembelajaran Berbasis Masalah dan Model Pembelajaran Kooperatif tipe ThinkPair-Share (TPS). Penelitian ini bertujuan untuk melihat pengaruh model pembelajaran ditinjau dari gaya belajar terhadap kemampuan berpikir kritis. Penelitian ini dilakukan di SD ABC dengan jumlah populasi 153 siswa di kelas II SD. Metode penelitian ini adalah penelitian kuantitatif dengan menggunakan kuasi eksperimen. Analisis data diuji menggunakan uji normalitas dan homogenitas. Pengujian hipotesis menggunakan ANAVA dua jalur serta uji Tukey. Kesimpulan yang didapatkan adalah adanya perbedaan hasil kemampuan berpikir kritis antara siswa yang mendapatkan pembelajaran dengan Model Pembelajaran Berbasis Masalah dan Model Pembelajaran Kooperatif tipe TPS dengan taraf signifikansi 0,017, tidak ada perbedaan kemampuan berpikir kritis siswa dengan gaya belajar auditori antara siswa yang mendapatkan pembelajaran dengan Model Pembelajaran Berbasis Masalah dan Model Pembelajaran Kooperatif tipe ThinkPair-Share dengan nilai signifikansi 0,211, dan tidak ada perbedaan kemampuan berpikir kritis siswa dengan gaya belajar kinestetik antara yang mendapatkan pembelajaran dengan Model Pembelajaran Berbasis Masalah dan Model Pembelajaran Kooperatif tipe Think-Pair-Share dengan nilai signifikansi 0,421.